13. Rex Leonard Burch: Humane Scientist and Gentle Man. Issue 5 (November 2014) - Balls, Michael
Rex Burch played a vital role in collecting background information about practical animal experimentation, and was the first person to use the term 'alternatives' in that context. The senior author of The Principles, William Russell, greatly valued their collaboration